Causal Relations among Macroeconomic Variables under Various Exchange Rate Levels: An Implementation of Threshold Vector Autoregression Model - Teker, Dilek; Teker, Suat; Aykac Alp, Elçin (International Journal of Economics and Financial Issues, 2018)
The paper examines interaction between selected macroeconomic determinants such as exchange rates, stock exchange market indexes, gold prices, money supply and inflation rates. Considering a nonlinear relationships in various macroeconomic indicators, a Threshold Vector Autoregression (TVAR) model is implemented. The data covers a period from 2003:01 to 2017:07. The results of the analysis points out the relationship between those macroeconomic indicators above and below the specific threshold value for exchange rate. The estimations indicate that policy maker may use monetary variables as policy variable for the stability of this system if they do not ignore the level of exchange rate. Keywords: threshold vector autoregression model, exchange rate transmission JEL Classifications: C32, E31, E44